2017
DOI: 10.3847/1538-4357/835/1/52
|View full text |Cite
|
Sign up to set email alerts
|

Massive Warm/Hot Galaxy Coronae as Probed by Uv/X-Ray Oxygen Absorption and Emission. I. Basic Model

Abstract: We construct an analytic phenomenological model for extended warm/hot gaseous coronae of L * galaxies. We consider UV OVI COS-Halos absorption line data in combination with Milky Way X-ray OVII and OVIII absorption and emission. We fit these data with a single model representing the COS-Halos galaxies and a Galactic corona. Our model is multi-phased, with hot and warm gas components, each with a (turbulent) lognormal distribution of temperatures and densities. The hot gas, traced by the X-ray absorption and em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
162
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(179 citation statements)
references
References 122 publications
(172 reference statements)
17
162
0
Order By: Relevance
“…Both observations and theoretical models imply that the gas density in the CGM falls with radius roughly like r −1 to r −1.5 (Maller & Bullock 2004;Miller & Bregman 2013Werk et al 2014;Voit et al 2017;Faermon et al 2017). When we take an initial radial density profile for the volume-filling phase of n vf ∝1/r, and following the self-similar solutions for energy-driven bubbles in Dyson (1989), the radius of the expanding bubble is given by ), M hot,10 is the total mass of the volume-filling phase out to a radius of 200 kpc in units of 10 10 M e , and t 8 is the time since the starburst began, given in units of 10 8 years.…”
Section: A Two-phase Cgmmentioning
confidence: 97%
“…Both observations and theoretical models imply that the gas density in the CGM falls with radius roughly like r −1 to r −1.5 (Maller & Bullock 2004;Miller & Bregman 2013Werk et al 2014;Voit et al 2017;Faermon et al 2017). When we take an initial radial density profile for the volume-filling phase of n vf ∝1/r, and following the self-similar solutions for energy-driven bubbles in Dyson (1989), the radius of the expanding bubble is given by ), M hot,10 is the total mass of the volume-filling phase out to a radius of 200 kpc in units of 10 10 M e , and t 8 is the time since the starburst began, given in units of 10 8 years.…”
Section: A Two-phase Cgmmentioning
confidence: 97%
“…Dai et al 2012;Bogdán et al 2013;Anderson, Churazov & Bregman 2016). By combining observations of Ovi absorbers around star-forming galaxies (from the COS-Halos survey, see below) together with the Ovii and Oviii absorption associated with our Galaxy in a single model of corona, Faerman, Sternberg & McKee (2017) found that the typical coronal gas mass of a Milky-Way-like galaxy is ∼ 1.35 × 10 11 M . Regarding the cooler phase of the CGM, Hi observations in the Milky Way revealed a population of HVCs, characterized by velocities inconsistent with the rotation of the Galactic disc (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…where we used Λ = Λ ⊙ (T, n)Z ′ , ignoring cooling by hydrogen and helium and resulting in a lower limit for the cooling time. Given the shape of the cooling function and the OVI 8 In Faerman et al (2017) we used the isobaric cooling time, longer by a factor of 5/3 and t dyn = r 3 /GM, shorter by √ 2. Thus, the ratio t cool /t dyn from FSM17 should be scaled down by ≈ 2.35 to compare with the values adopted here.…”
Section: Timescalesmentioning
confidence: 99%